PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK HOMEROOM TERHADAP MINAT BELAJAR SISWA - Adi Marsono; Evi Afiati; Putri Dian Dia Conia (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2022)
The background of this study is based on an interview and when a preliminary study was done by the researcher, the results found that there are still occurred low learning interest by some student in class X student of SMA Negri 1 Baros kabupaten serang academic year 2021/2022). The purpose of this study is to determine the effectiveness of group guidance with homeroom technique to upgrade the student learning interest. This study used a pre-experimental method with one group pre-test and post-test design. The sample selection used a purposive sampling method. The subject research consists of 8 students with low learning interest category. The method of data selection got by questionnaire. The results of this study showed that the average value before treatment/pre-test is 38 with 34% presentations and the average value after treatment/post-test is 81 with 82% percentations. Based on pre-test and post-test results, obtained an average gain score of 44, its definite that the homeroom technique is effective to upgrade student learning interest to class X students of SMA Negri 1 Baros kabupaten serang academic year 2021/2022.